The Iceland–Jan Mayen plume system and its impact on mantle dynamics in the North Atlantic region: Evidence from full-waveform inversion - Rickers, Florian; Fichtner, Andreas; Trampert, Jeannot (Elsevier, 2013)
We present a high-resolution S-velocity model of the North Atlantic region, revealing structural features in unprecedented detail down to a depth of 1300 km. The model is derived using full-waveform tomography. More specifically, we minimise the instantaneous phase misfit between synthetic and observed body- as well as surface-waveforms iteratively in a full three-dimensional, adjoint inversion. Highlights of the model in the upper mantle include a well-resolved Mid-Atlantic Ridge and two distinguishable strong low-velocity regions beneath Iceland and beneath the Kolbeinsey Ridge west of Jan Mayen. A sub-lithospheric low-velocity layer is imaged beneath much of the oceanic lithosphere, consistent with the long-wavelength bathymetric high of the North Atlantic. The low-velocity layer extends locally beneath the continental lithosphere of the southern Scandinavian Mountains, the Danish Basin, part of the British Isles and eastern Greenland. All these regions experienced post-rift uplift in Neogene times, for which the underlying mechanism is not well understood. The spatial correlation between the low-velocity layer and uplifted regions suggests dynamic support by low-density asthenosphere originating from the Iceland and Jan Mayen hotspots. Our model further suggests a lower-mantle source for the Iceland and Jan Mayen hotspots. Two distinguishable low-velocity conduits are imaged, connecting the upper-mantle anomalies beneath Iceland and Jan Mayen into the lower mantle. Both conduits are tilted to the South-East, reflecting the westward motion of the Mid-Atlantic Ridge. The location of the imaged Iceland conduit is in agreement with the observation of a locally thinned transition zone south of Iceland from receiver function studies. ISSN:0012-821X ISSN:1385-013X